53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-1961
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic Cavity Control Using Plasma Actuators

Abstract: Cavity flows are present in a wide range of aerodynamic applications. A cavity could potentially be used in a scramjet isolator as a shock trap to increase the back-pressure margin of the inlet/isolator. In order to avoid a significant drag penalty while maintaining shock-trapping ability, fastresponse resonance suppression is required. Localized Arc Filament Plasma Actuators (LAFPAs) have demonstrated the ability to control a high subsonic cavity flow. 1 This work investigates the control authority of the LAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This procedure makes it difficult to precisely match the peak tone, therefore it is likely that resonance is suppressed in some cases, as near frequency-matching has been observed to suppress resonance. 13 The cavities with slanted aft walls exhibited no natural resonance; therefore to determine the theoretical "optimum enhancement" frequency for excitation an alternate method was required. For these cases, the frequency observed in the rectangular cavity of the most similar length was scaled to the appropriate length (halfway up the slanted aft wall).…”
Section: Back-pressure Margin Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure makes it difficult to precisely match the peak tone, therefore it is likely that resonance is suppressed in some cases, as near frequency-matching has been observed to suppress resonance. 13 The cavities with slanted aft walls exhibited no natural resonance; therefore to determine the theoretical "optimum enhancement" frequency for excitation an alternate method was required. For these cases, the frequency observed in the rectangular cavity of the most similar length was scaled to the appropriate length (halfway up the slanted aft wall).…”
Section: Back-pressure Margin Resultsmentioning
confidence: 99%
“…The same geometries as previously studied were reassessed, this time for a baseline case and 2 excited cases: resonance suppression and resonance enhancement. The previously observed 13 best-case resonance suppression (16.7 kHz, 3-D excitation) parameters were used for all geometries. For the resonance excitation case, the frequency was matched (manually) to the peak tone frequency observed at the time of the run.…”
Section: Back-pressure Margin Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done by attempting to excite/suppress the natural shear layer (Rossiter) resonance characteristics of the cavity. Webb et al 71,72 showed in both cases that this was possible and could be effective. However more work is necessary to improve the understanding of how this mechanism works.…”
Section: Applications Of Lafpa'smentioning
confidence: 99%
“…There has been some interest in the application of LAFPA's to augment the shear layer resonance of supersonic cavity flows. Webb et al 71,72 investigated this application. The objective of these studies was to augment the shock-trapping capabilities 73 of cavities within a supersonic isolator.…”
Section: Applications Of Lafpa'smentioning
confidence: 99%